2021
DOI: 10.6018/rcsar.363171
|View full text |Cite
|
Sign up to set email alerts
|

Readabilty in management reports: extension and good governance practices

Abstract: La legibilidad en los informes de gestión: extensión y buenas prácticas de gobierno corporativo. Este estudio expande el conocimiento sobre la legibilidad de los informes contables, su extensión y el cumplimiento de las empresas con las prácticas de buen gobierno. También cubre un vacío en el análisis de la legibilidad de la información narrativa escrita en español. Examinamos la legibilidad en los Informes de Gestión de las empresas españolas que cotizan en el Mercado Continuo de la Bolsa de Madrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(135 reference statements)
1
4
0
1
Order By: Relevance
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…In this sense, as Yamane and Kaneko (2021) showed, raising stakeholder awareness of the SDGs leads private companies to engage in SDG implementation. In particular, due to the increase in the institutional investors' participation in listed companies' ownership, which ascends to more than 40% (Organisation for Economic Co‐operation and Development ‐ OECD, 2020), they significantly influence corporate strategies, including SDG engagement and reporting (Calza et al, 2016; García‐Sánchez, Rodríguez‐Ariza, Aibar‐Guzmán, & Aibar‐Guzmán, 2020; Hadro et al, 2021; Jonsdottir et al, 2021; Melón‐Izco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, as Yamane and Kaneko (2021) showed, raising stakeholder awareness of the SDGs leads private companies to engage in SDG implementation. In particular, due to the increase in the institutional investors' participation in listed companies' ownership, which ascends to more than 40% (Organisation for Economic Co-operation and Development -OECD, 2020), they significantly influence corporate strategies, including SDG engagement and reporting (Calza et al, 2016;Hadro et al, 2021;Jonsdottir et al, 2021;Mel on-Izco et al, 2021). Indeed, introduced in April 2006, the United Nations Principles for Responsible Investment (UN PRI) establish commitments to incorporate social, environmental, and governance criteria into investment decisions (Cohen et al, 2011), encouraging Socially Responsible Investment (SRI) and investors' activism to promote sustainability in the companies in which they invest (García-Sánchez, Aibar-Guzmán, & Aibar-Guzmán, 2020).…”
mentioning
confidence: 99%
“…The procedure used to obtain the information necessary to achieve our objective was based on content analysis [47][48][49] from publicly available information from the sample companies' corporate websites. The main sources of information were annual reports, integrated reports, CSR reports, sustainability reports, corporate governance reports, conduct codes, and specific sections of the companies' websites related to employees, suppliers, customers, and shareholders.…”
Section: Methodsmentioning
confidence: 99%